Nothing New Under the Sun? The Study of Biblical Hebrew in the Era of Generative Pre-trained AI - Elrod, A. G. (HIPHIL Novum, 2023)
This article investigates the potential impact of generative artificial intelligence, specifically OpenAI's GPT, on the field of biblical studies, particularly biblical Hebrew. The study is divided into three main categories: (1) knowledge retrieval or language understanding, (2) generative modeling or creative problem solving, and (3) command interpretation or query parsing. Experiments are conducted using OpenAI's GPT, the ETCBC's BHSA dataset, and Text-Fabric Python libraries. Results demonstrate GPT's limitations and proficiencies in biblical Hebrew and its capacity to employ its proficiencies creatively in problem-solving scenarios involving multifaceted forms of reasoning. The study concludes that understanding the capabilities and potential trajectories of these technologies is vital for biblical Hebrew scholarship, as they already possess the capacity to disrupt established scholarly norms and democratize access to advanced tools.